COMPARISON OF SEROLOGICAL TESTS AND PCR FOR DIAGNOSIS OF HUMAN BRUCELLOSIS SUFFERING FROM FEVER - Kuila, Prabir; Dutta, Devarati; Chakrabarty, Urmita; Chatterjee, Debasmita; Das, Satadal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Brucellosis is an important zoonotic disease throughout the globe and other developing countries. The present study was aimed to compare results of different serological tests and PCR for diagnosis of brucellosis in patients sufferings from fever in Kolkata and in adjoining districts. Methods: A total of 2088 serum samples were collected from the patients suffering from fever from January, 2013 to September, 2015. The samples were tested by serological tests STAT, RBPT, ELISA(IgM,IgG) and Brucella genus specific PCR. Results: The study revealed decreasing positive results by STAT (18.43%, N=385), RBPT (12.59%, N=263), IgM ELISA (7.71%, N=161), PCR (4.21%, N=88) and IgG ELISA (1.43%, N=30). When serological tests were compared with PCR, it was found that both STAT and PCR were positive in 84 samples( 4.02%), both RBPT and PCR were positive in 65 samples(3.11%), both IgM and PCR were positive in 51 samples(2.44%) and both IgG and PCR were positive in 9 samples(0.43%). Conclusion: In this cross sectional study in a zonal population of India it was found that STAT was the most sensitive test for diagnosis of brucellosis followed by RBPT when compared to PCR test results. Four STAT negative samples showed positive results in PCR, which were positive by RBPT test. This indicates that if we combine STAT and RBPT for diagnosis of brucellosis then both sensitivity and specificity of the combined test will increase. Â